Application of Personal Branding As a Campus “Bela Negara” at UPN “Veteran” East Java - E. Poernomo; R. Hidayat; R. R. Prayogo (Future Science)
The application of personal branding has become a central element in new management practices throughout the University. Personal branding plays a role in shaping the differentiation produced by a university. Personal branding is considered important for the sustainability of an organization in introducing brands in the community. Some organizations continue to improve and introduce personal branding, including universities in Indonesia. One of the higher education that has strong personal branding is the East Java National Development University 'UPN' East Java. UPN